Influence of Technology Availability and Ease of Use on Academic Achievement with Behavioral Control, Usefulness, and Subjective Norm as Mediators - Hengki Mangiring Parulian Simarmata; Doris Yolanda Saragih; Andy Wijaya; Elfina Okto Posmaida Damanik (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
This study aims to analyze the influence of Technology Availability and Perceived Ease of Use on Academic Achievement with mediating variables of Perceived Behavior, Perceived Usefulness, and Subjective Norm. A qualitative approach with an explanatory design was used in this study. The research population consists of all students at Politeknik Bisnis Indonesia who actively use technology in academic activities, with a sample of 130 respondents selected through a purposive sampling technique. The research results show that Technology Availability has a significant positive effect on Perceived Behavioral Intention (T-Statistic 8.412; P-Value 0.000) and Perceived Usefulness (T-Statistic 3.249; P-Value 0.001). Perceived Ease of Use shows a significant positive effect on Perceived Usefulness (T-Statistic 10.875; P-Value 0.000) and Subjective Norm (T-Statistic 11.476; P-Value 0.000). These results support the Technology Acceptance Model (TAM) theory. Additionally, Perceived Behavioral Intention and Perceived Usefulness each have a significant positive effect on Academic Achievement (T-Statistic 3.382; P-Value 0.001, T-Statistic 2.422; P-Value 0.016). However, Subjective Norms do not have a direct impact on Academic Achievement. (T-Statistik 1,452; P-Value 0,147). These findings highlight the importance of technology availability and perceived ease of use in enhancing students' academic performance by meditating on behavioural intention and perceived benefits. Recommendations are given for improving access and technology training in educational environments to maximize the use of technology in learning.